Expressing thinking in institutional interaction: Stancetaking in mental health rehabilitation group discussions - Paananen Jenny; Stevanovic Melisa; Valkeapää Taina (Netherlands, 2022)
This paper focuses on the stancetaking formats used to express personal thoughts, namely Finnish mä aattelen/aattelin ‘I think/thought’, mä mietin ‘I think/wonder’, and mun mielestä/musta ‘I think/in my opinion’. We study how these first-person formats are used in mental health rehabilitation group meetings, which aim to promote joint decision-making. In particular, we analyze whether the institutional asymmetry between support workers and clients is reflected in the use of these thought expressions. Our data comprise 23 video-recorded rehabilitation meetings, and the adopted methods are conversation analysis and interactional linguistics.
Most of the stancetaking formats in our data are produced by support workers (106/129). The results of a sequential analysis conducted in this study demonstrate that support workers' thought expressions are embedded in their institutional actions, which are beyond the clients' authority. Moreover, our data suggest that support workers' and rehabilitants' thought expressions generate different participation dynamics. Although previous research has considered I think-formats typically as calls for other views, in institutional settings such as ours, these formats can also be interpreted as highlighting an institutional agent's controlling position. Acknowledging the existence of such differences in stancetaking practices can advance the design of new protocols to facilitate client participation.